2016
DOI: 10.18203/2320-1770.ijrcog20164660
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards emergency contraception in females of urban area of Lucknow, Uttar Pradesh, India

Abstract: Background: Emergency contraception are birth control measures that, if taken after unprotected sexual intercourse, contraceptive failure, incorrect use of contraceptives or in cases of sexual assault may prevent pregnancy. The aim of the study was to assess the knowledge and attitude of female living in urban part of Lucknow district from September 2015 to August 2016.Methods: This was a descriptive, cross-sectional study conducted at RML Hospital, Lucknow from September 2015 to August 2016. A cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
2
1
1
Order By: Relevance
“…A study at Tigray, Ethiopia by Gebrehiwot et al [25] showed association with the private college students with the knowledge level. A study at Lucknow, India, by Mishra et al [26] showed significant association with the religion, and the study by Hoque et al [19] in South Africa showed significant association with the day's scholar with the knowledge level similar to our study. The Mangalore study by Joseph et al [16] showed a significant association with the gender which is against our study results and no association with the place of matriculation and the knowledge level which is similar to our study.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A study at Tigray, Ethiopia by Gebrehiwot et al [25] showed association with the private college students with the knowledge level. A study at Lucknow, India, by Mishra et al [26] showed significant association with the religion, and the study by Hoque et al [19] in South Africa showed significant association with the day's scholar with the knowledge level similar to our study. The Mangalore study by Joseph et al [16] showed a significant association with the gender which is against our study results and no association with the place of matriculation and the knowledge level which is similar to our study.…”
Section: Resultssupporting
confidence: 89%
“…A study in Adama, Ethiopia, also showed a significant association between the age of the participants, marital status and religion with the attitude level [18]. Another study at Uttar Pradesh, India, also showed association with the course of study and religion with the awareness level of the participants [26]. In our study, the participants with a positive attitude are significantly and most likely to have moderate awareness regarding EC.…”
Section: Resultssupporting
confidence: 71%
“…Also, 68% of the participants in this study knew the correct time frame to use EC. This finding is lower than the finding of the study conducted in Tamale (85%) [ 24 ] and in Arba Minch, Ethiopia (87.2%) [ 32 ], but higher than studies conducted in Botswana (38.2%) [ 23 ], Southern Ethiopia (51.5%) [ 26 ], Uttar Pradesh (54%) [ 33 ] and Nagpur district (46%) in India [ 30 ]. However, the study in Nigeria (66.7%) [ 31 ] and in Harar Town, Ethiopia (65%) [ 1 ] showed similar proportions with the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…10 Community based cross-sectional study by Rikar conducted in 286 married women in age group 15-45 yrs residing in the field practice area of Urban Health Centre attached to Department of Community Medicine, Bagalkot, Karnataka, only 12% had knowledge of EC which was much lower than current study (66%). 11…”
Section: Discussionmentioning
confidence: 99%